Sistem Multi Level Marketing Di Skincare Nu Amoorea Dalam Persfektif Fatwa MUI - Izzan, Ahmad; Sopiah, Suci (Jurnal Hukum Ekonomi Syariah, 2022)
Multi-Level Marketing (MLM) is a trading or marketing method of selling a product to customers using a recruitment network developed by distributors, and this MLM system is tiered. This MLM system is practiced by one company in Indonesia, PT. DEP, which markets beauty products or skincare products Nu Amoorea. In practice, does it comply with the DSN-MUI Fatwa No. 75 of 2009 or not? The research problems in this study are: 1) What is the multi-level marketing system in Skincare Nu Amoorea? 2) How is the multi-level marketing system in Skincare Nu Amoorea viewed from the perspective of MUI Fatwa? The research objectives are: 1) To understand the multi-level marketing system in Skincare Nu Amoorea. 2) To understand the multi-level marketing system in Skincare Nu Amoorea from the perspective of the MUI Fatwa. This research is a field research and qualitative research. Data collection techniques used are interviews, literature reviews, and documentation. The results of the study conclude that the MLM system in Skincare Nu Amoorea is through giving bonuses (PSB, NDB, NLB, NBB) and it does not meet 6 out of 12 criteria of the MUI Fatwa, namely: In point 3, there is still an element of unfairness in bonus distribution. In point 4, there is excessive pricing that burdens consumers. In point 5, there is bonus distribution based on downline productivity. In point 7, there is passive income. In point 9, there is unfairness in bonus distribution, and in point 12, there is a presence of a money game.  Keywords: Multi-Level Marketing, Skincare Nu Amoorea, MUI Fatwa Perspective.